Preparation and Clinical Evaluation of 99mTc-dimercapto Succinic Acid (99mTc-DMSA), Freeze-dried Kit For Kidney Cortex Scintigraphy (Al Mustansiriyah Journal of Pharmaceutical Sciences, 2009)
99mTc-dimercapto Succinic acid freeze-dried kit(99mTc-DMSA) was prepared by reaction of kit that is contained (1mg of 2.3 meso dimercaptosuccinic acid,0.336 mg of stannous chloride, 40mg insitol and 0.9 ascorbic acid as anti oxidant) with Na99mTcO4 at pH equal to (2-4) that is the optimal condition to formation 99mTc-DMSA complex.The radiochemical purity and stability of 99mTc-DMSA in liquid and dried forms were determined on gel filtration column scanning “GCS”. The labeling yield of complex formation was greater than 99% after 15 min. from addition of Na99mTcO4. The complex in liquid form was stable during ten hours while in lyophilized form six months.The biodisribution of kit was studied on white male mice that the results indicate to the ratio of dose concentration accumulated into kidneys is greater than29% of injected dose, however, little amounts of complex was detected in non target organs.